Dapur CikguRu: Better Taste / Hanis Hasanah Nor Azman - Nor Azman, Hanis Hasanah (2021)
Better Taste is a sole proprietorship business that was established by Hanis Hasanah binti Nor Azman on April 15th, 2021. The nature of Better Taste's business is food, and the target market is not limited to youth, but includes people of all ages. It is because any food does not have to be age specific. Better Taste's food is suitable for all ages. The product that I have decided to focus on was Anchovy Floss or “Serondeng Ikan Bilis” that are made by Dapur CikguRu. They are titled Dapur CikguRu and are produced by the onwer's mother. It is made using fresh ingredients, from the anchovies to the onions to the chilies, and it takes a long time to mix the anchovy floss until it is dry. As a result, patience is required. Facebook was chosen as the main platform for Better Taste to promote is because Facebook offers so many benefits and opportunities for business owners. Facebook is a low-cost marketing technique that is ideal for small to medium-sized businesses with a restricted marketing budget. Better Taste frequently posts soft sell and hard sell content on Facebook in order to engage with customers and cater to the market for product purchases.